2009
DOI: 10.1074/jbc.m109.028902
|View full text |Cite
|
Sign up to set email alerts
|

S-Glutathionylation of the Rpn2 Regulatory Subunit Inhibits 26 S Proteasomal Function

Abstract: Although increased intracellular concentrations of hydrogen peroxide (H 2 O 2 ) are associated with inhibition of 26 S proteasomal activity, the mechanisms responsible for such effects have not been well delineated. In the present studies, we found that direct exposure of purified 26 S proteasomes to H 2 O 2 had negligible effects on their activity, whereas incubation with glutathione and H 2 O 2 produced >80% decrease in chymotrypsin-like and trypsin-like activities. Rpn1 and Rpn2, which are subunits of the 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(46 citation statements)
references
References 68 publications
1
44
0
1
Order By: Relevance
“…The Kir6.1 S-glutathionylation was further tested with the streptavidin pull-down assay (26). The A10 vascular smooth muscle cell line, in which the Kir6.1/SUR2B channel was endogenously expressed (17,27), was loaded with BioGEE (250 M) for 1 h followed by an H 2 O 2 (750 M) challenge for 15 min.…”
Section: H 2 O 2 Impaired Pinacidil-induced Vasodilation In Isolatedmentioning
confidence: 99%
“…The Kir6.1 S-glutathionylation was further tested with the streptavidin pull-down assay (26). The A10 vascular smooth muscle cell line, in which the Kir6.1/SUR2B channel was endogenously expressed (17,27), was loaded with BioGEE (250 M) for 1 h followed by an H 2 O 2 (750 M) challenge for 15 min.…”
Section: H 2 O 2 Impaired Pinacidil-induced Vasodilation In Isolatedmentioning
confidence: 99%
“…S-glutathionylation of S100A9 regulates its inflammatory activity in neutrophils (Lim et al, 2010). In another study, it was found that increased levels of H 2 O 2 results in diminished proteasomal activity of 26S proteasome via S-glutathionylation of its regulatory subunit Rpn2 (Zmijewski et al, 2009). A recent report describes how stimulated neutrophils present deglutathionylated actin and associated polymerization, neutrophil polarization, chemotaxis, adhesion and phagocytosis.…”
Section: Diabetic Animal Models and S-glutathionylationmentioning
confidence: 99%
“…Western blot analysis was performed as previously described (9,22). Briefly, cell lysates of neutrophils (3.5 × 10 6 / well), macrophages (2 × 10 5 /well) or MCF7 cells (10 5 /well) were prepared using lysis buffer containing Tris pH 7.4 (50 mmol/L), NaCl (150 mmol/L), Nonidet P40 (NP-40) (0.5%, vol/vol), ethylenediaminetetraacetic acid (EDTA) (1 mmol/L), ethyleneglycotetraacetic acid (EGTA) (1 mmol/L), okadaic acid (1 nmol/L) and protease inhibitors.…”
Section: Western Blot Analysismentioning
confidence: 99%